Perturbations in Endocytotic and Apoptotic Pathways Are Associated With Chemotherapy-Induced Nausea. Issue 2 (April 2021) - Singh, Komal; Cao, Huangshen; Miaskowski, Christine; Conley, Yvette P.; Hammer, Marilyn; Wright, Fay; Levine, Jon D.; Kober, Kord M.
Background: While vomiting is well controlled with current antiemetic regimens, unrelieved chemotherapy-induced nausea (CIN) is a significant clinical problem. Perturbations in endocytotic and apoptotic pathways in the gut can influence the functioning of the microbiome-gut-brain-axis and the occurrence of gastrointestinal (GI) symptoms. However, limited information is available on the mechanisms that underlie unrelieved CIN. Objectives: The purpose of this study was to evaluate for perturbed biological pathways associated with endocytosis and apoptosis in oncology patients who did (n = 353) and did not (n = 275) report CIN prior to their second or third cycle of chemotherapy (CTX). Methods: Oncology patients (n = 735) completed study questionnaires in the week prior to their second or third cycle of CTX. CIN occurrence was evaluated using the Memorial Symptom Assessment Scale. Pathway impact analyses (PIA) were performed in 2 independent samples using RNA-sequencing (sample 1, n = 334) and microarray (sample 2, n = 294) methodologies. Fisher's combined probability method was used to identify signaling pathways related to endocytotic and apoptotic mechanisms that were significantly perturbed between the 2 nausea groups across both samples. Results: CIN was reported by 63.6% of the patients in sample 1 and 48.9% of the patients in sample 2. Across the 2 samples, PIA identified 4 perturbed pathways that are involved in endocytosis (i.e., endocytosis, regulation of actin cytoskeleton) and apoptosis (i.e., apoptosis, PI3K/Akt signaling). Conclusions: Our findings suggest that CTX-induced inflammation of the GI mucosa, that results in the initiation of endocytotic and apoptotic processes in the gut, is associated with the occurrence of CIN.